Идеальный друг: роман / Мартин Сутер - Сутер Мартин (The best of Иностранка, 2007)
Экземпляры: ф.14 (2007) / Инвентарный номер: 50990 / Цена: / Сис.шифр: 84(4Шва)-4 / Авт.знак: С 90 / ГРНТИ: 17.82.31 / ББК: 84(4Шва)-44